(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
The systematic relationships of Krameriaceae have changed considerably. The phylotranscriptomic data sets provide highly informative data for resolving deeper‐level phylogenetic relationships. The phylotranscriptomic analyses to infer evolutionary relationships of Krameriaceae in the order Zygophyllales using the Minimum Evolution, Maximum Parsimony and Maximum Likelihood methods recovered similar topology and taxon proximity. Under the Zygophyllales clade, Krameria lanceolata Torr. of the family Krameriaceae nested with Tribulus eichlerianus K.L. Wilson and Larrea tridentata (Sessé & Moc. ex DC.) Coville belonging to the family Zygophyllaceae with strong nodal support. The phylotranscriptomic analyses suggest that the family Krameriaceae is sister to Zygophyllaceae. Bangladesh J. Plant Taxon. 27(2): 427-433, 2020 (December)